(untitled) (Journal of Interdisciplinary Insights, 2024)
This paper explores the concept of New Quality Productivity (NQP) as a strategic shift in China’s economic development towards a more sustainable and innovation-driven model. In response to global trends emphasizing technology, digitalization, and environmental sustainability, China has recognized the limitations of its traditional growth model, which heavily relied on resource-intensive industries and labor-driven expansion. NQP represents a qualitative leap in productivity, focusing on technological breakthroughs, efficient resource use, and high-quality development. The paper examines the core elements of NQP, including technological innovation, integration with new industries, and the role of data as a key production factor. It further analyzes the pathways for developing NQP, highlighting key sectors such as new energy, new materials, digital technology, biomedicine, and high-end equipment manufacturing. Challenges in transitioning to this new model, such as reducing reliance on resource-intensive industries and closing technological gaps, are discussed. The strategic significance of NQP for China’s modernization goals by 2035 is also considered, emphasizing its potential to enhance China’s international competitiveness and align with global economic and technological trends. By embracing NQP, China aims to secure its long-term economic vitality, promote sustainable growth, and contribute to global efforts in technological advancement and environmental sustainability.